TECHNOLOGY OF CULTURE FORMATION OF PEDAGOGICAL COMMUNICATION OF FUTURE TEACHERS - O.V. Lysevych (Academy of Cognitive and Natural Sciences, 2009)
The author emphasizes the necessity of using the pedagogical technology as an effective means of formation of the culture of pedagogical communication of future teachers.